The impact of in-situ urbanization on residents’ health: evidence from CFPS - Wu, Wei; Zhang, Shuoxuan; Zhao, Lei; Gao, Jiawei (Frontiers in Public Health, 2025)
This study investigates the health effects of in-situ urbanization utilizing panel data from the China Family Panel Studies (CFPS) tracking surveys of 2010, 2012, and 2014. Employing a difference-in-differences (DID) model, the analysis reveals a statistically significant positive impact of in-situ urbanization on individual health. Specifically, individuals subjected to in-situ urbanization policies exhibit a 6.7% reduction in the reported incidence of physical discomfort within the preceding two weeks. Heterogeneity in the health effects of in-situ urbanization is observed across demographic strata, including gender, age, and educational attainment. Notably, the health-enhancing effects are more pronounced for female respondents compared to their male counterparts. Furthermore, a discernible age-related disparity is evident, with individuals below the age of 60 demonstrating significant health improvements, while those aged 60 and above do not manifest statistically significant health gains. In terms of educational attainment, individuals with educational levels below high school experience a greater magnitude of health improvement attributable to in-situ urbanization. The mechanism through which in-situ urbanization improves individual health is mediated by an increase in household income. Structurally, this income augmentation is characterized by an increase in operating and property income, coupled with a concomitant decrease in transfer income. Consequently, the elevation of operating and property income emerges as a salient intermediate mechanism facilitating the health improvement effects of in-situ urbanization.